Initial surmises from a field study of suction behaviour of tropical unsaturated residual soils - Singh, Harwant; Kim Huat, Bujang; Ali, Faisal; Mariappan, Saravanan (Electronic Journal of Geotechnical Engineering, 2009)
The generally unsaturated residual soils segment located above the groundwater table possess negative pore-water pressures. This amount of water content and resulting matric suction is an important geotechnical relationship for the unsaturated residual soil. This paper describes a field study that examined the water content and matric suction in the unsaturated weathered residual soil over one of the commonly found soil/rock types constituting the tropical Malaysian terrain i.e. residual soil over sandstones at various weathering grades. The soilwater characteristic curve (SWCC) was found to be characterized by two distinct curves, a wetting (sorption) curve and a drying (desorption) curve, each showing distinctive water retention propensity. Higher weathering grades appear to have a higher suction for a given water content.